CREATION OF ASSESSMENT CENTER FOR QNP COMPANY - Aryslan, Aitbayev; Nazar, Ulpa; Aigerim, Samarkhanova; Elmira, Bakytkhanova (Nazarbayev University, Graduate School of Business, 2023)
This practicum project explores the unique needs of "Qazaq National Product" LLP, a specialized industrial safety consulting company in Kazakhstan. The company has specified key outcomes, including the development of a competency model and enhancements to the regulations governing the employee performance evaluation system, all based on this model. The company's strategic objective includes the establishment of an assessment center to enhance candidate selection, assess employee potential, and build a robust talent pool. The research methodology involved an in-depth analysis of internal standards, extensive stakeholder consultations, and empirical data gathering to pinpoint pivotal competencies critical to success in industrial safety consulting. The proposed competency model offers a strategic framework for identifying high-potential employees and establishing a robust talent pipeline. The practicum project incorporates two distinct methodologies, Psychological Capital (PsyCap) and the International Project Management Association (IPMA), to assess employee competencies. PsyCap focuses on positive psychological attributes contributing to employee well-being and performance, while IPMA emphasizes project management competencies aligning with the company's project-oriented structure. Surveys were designed to assess project managers, covering job satisfaction, leadership, and PsyCap. The strategic analysis tools, including SWOT analysis, Porter's Five Forces, and the 7S framework, provide insights into the company's internal and external factors. The SWOT analysis identified strengths such as technical expertise and financial support, weaknesses like underdeveloped incentive systems, opportunities in developing a project management system, and threats related to changes in the CIS markets. The research question focuses on evaluating the effectiveness of the current assessment center at QNP Education, aiming to improve the employee performance evaluation system based on the developed competency model. The methodology utilizes Psychological Capital and IPMA, with three surveys designed for project managers. IPMA's "Eye of Competence" model categorizes competencies into People, Practice, and Perspective, providing a comprehensive framework for assessment. The situation analysis delves into the history and structure of Qazaq National Product, its mission, and the specific challenges it faced, leading to the collaboration with the Nazarbayev University Graduate School of Business for consultancy on the creation of an assessment center. The practicum project proposes a research question focused on evaluating the effectiveness of the current assessment center implemented by QNP Education for identifying core competencies in employees. The findings indicate the integration of PsyCap and IPMA in the competency model, aligning with best practices in assessing psychological attributes and project management competencies. The recommended methodology involves using an integrated approach that combines continuous competency review, enhanced data analytics, and phased 360-degree feedback implementation. This comprehensive strategy is designed to enhance the assessment center's effectiveness and align with the organization's strategic goals. The measures of effectiveness are categorized into the customer, internal, innovation and learning, and financial perspectives of the Balanced Scorecard. They highlight the impact of assessment centers on employee competence, customer satisfaction, talent management, employee development, training, and cost efficiency.
Keywords: Competency Model; Industrial Safety Consulting; Assessment Center; Balanced Scorecard; Type of access: Restricted